Screen Jesus : portrayals of Christ in television and film - Malone, Peter (Lanham, Md. : Scarecrow Press, 2012)
Screen Jesus takes a close look at both mainstream and lesser-known films in which Jesus is depicted. In addition to providing a historical overview of the Jesus films, this book also reveals the changes in piety and the theological understandings of the humanity and divinity of Jesus over the decades. --from publisher description
Foreword / by Maggie Roux -- Introducing the theme -- The Jesus figure -- Biblical portraits of Jesus -- The Jesus films: the early 20th century -- The Jesus films: the 1920s and Cecil B. De Mille -- The Jesus films: the 1930s, 1940s and 1950s: Jesus' absence from the mainstream and evangelical Jesus-figures -- The Jesus films: the 1950s and 1960s: mainstream images -- The Jesus films: the 1960s -- The Jesus films: the 1970s -- The Jesus films: the 1980s -- The Jesus films: cinema freedom and images of Jesus -- The Jesus films: the 1990s -- The Jesus films: the 21st century -- The Jesus films: Jesus in our world today -- The Jesus films: verbal Jesus-figures -- Interest in Jesus and film beyond Christianity -- The reverent/serious -- The bizarre -- After The passion of the Christ.
Includes bibliographical references and index.
Keywords: Jesus Christ -- In motion pictures